Caracterização e desempenho de transformadores de estado sólido radiais multiferróicos - Montanher, Diogo Zampieri (2010)
In this work, it was developed a method for assembly radial vibration mode single-layer solid state transformers by using electrically isolated piezoelectric elements as actuators and transducers (primary and secondary). In this method we assembly two solid transformers, i. e., a ferroelectric one (ferroelectric solid state transformer - TRF) and a multiferroic one (multiferroic solid state transformer - TRM). The TRF transformer was composed by two PZT-5A ferroelectric ceramics, while the TRM transformer was composed by a PZT-5A ferroelectric ceramic and a (0.6)BiFeO3-(0.4)PbTiO3 multiferroic ceramic, or simply BF-PT. The physical characterization of these solid state transformers was carried out by experimental determinations of the gain voltage and the efficiency. The results were compared with a theoretical model found in literature, and presented a satisfactory agreement with the theoretical model, diverging in approximately 10%. In such a way, it was possible to verify the viability for using BF-PT multiferroic ceramics in the manufacture of solid state transformers by comparing the performance between both TRM and TRF devices. In this comparison we observe some similarities and differences between the solid state transformers formed by BF-PT multiferroic ceramics and those solid state transformers formed by PZT-5A ferroelectric ceramics, which are the ceramics widely used in the manufacture of these devices. In general, the electric behavior of the main properties of the TRM and TRF transformers are equal. However, the gain voltage and the efficiency possess different values. In comparison with the TRF transformer, the TRM one presented an average reduction of 1.7 times for the gain voltage, and an average reduction of 3.5 times for the efficiency. On the other hand, the transformer TRM can present magnetoelectrical properties that modify the gain of voltage and the efficiency according of an applied magnetic field, opening in a such a way new perspectives of application of these devices.